Organizational factors influencing the international sporting success in high-performance judo - Mazzei, L.; Böhme, M. T.; de Bosscher, V. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Researchers and managers have a great interest in analysing the existing sports policies in different countries in the search of explanations for the international sporting success achieved by some countries and not by others. Recently, the studies in this issue have further advanced studying certain aspects of elite sport policies and key success factors of specific sports (Brouwers, Sotiriadou, & De Bosscher, 2015). In this study, the objective was to identify the organizational factors that influence the international sporting success in high-performance Judo. Methods: A Sequential Exploratory Design (Creswell & Plano Clark, 2011) according was used, which involves an initial phase that collects and analyses qualitative data, followed by a second intermediate phase related to the development of a questionnaire and a third phase involves quantitative analysis. 33 international high-performance Judo stakeholders were interviewed in an initial phase. A questionnaire developed and validated by Content Validation of six experts was the second phase. And finally, in a third quantitative phase was performed an Exploratory Factor Analysis (EFA) on data obtained in a sample of 406 Brazilian judokas, divided into athletes, coaches, performance directors and experts. Results: In the qualitative phase, 11 categories and 44 subcategories were identified, which were considered the dimensions and the organizational factors influencing the international sporting success in high performance Judo respectively. From these results, in the second phase a questionnaire was developed, validated and allowed the quantitative phase. In the quantitative phase, all the organizational factors were in the EFA results. The first six Factors had the highest coherence with the qualitative results, contributing with 50.97% of the total variance. Discussion: The results found in the qualitative phase are similar to other studies that had the purpose of investigating elite sport policies and factors for the international sporting success. However, specific Judo characteristics and environment influence the development of Judo. Furthermore, the qualitative and quantitative phase allowed the development of the `Judo Organizational Factors Influencing the International Sporting Success` model. Future research can deepen the understanding of the relationship among organizational factors or carrying out procedures involving other sports. Future research can deepen the understanding of the relationship among organizational factors or carrying out procedures involving other sports.